FOSTERING PRODUCTIVITY: THE INTERPLAY OF WORK-LIFE HARMONY AND SOCIAL SUPPORT IN GENERATION Z - Sri Maitri, Wayan; Putra P, Komang Widhya Sedana (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
The given study investigates the impact of work-life harmony on productivity among Generation Z employees and further discusses whether this relationship is moderated by social support. The general objectives of this research are to investigate the influence of work-life harmony on productivity and to examine the influence of social support on such a relationship. A quantitative approach was followed; hence, the data collected from 150 respondents in Bali Province were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that work-life harmony significantly enhances productivity, thereby confirming the first hypothesis. Furthermore, social support from family, friends, and colleagues also positively moderates both work-life harmony and productivity, thus confirming the second hypothesis. These findings bring to the fore the necessity of recognizing that both work-life harmony and social support are interlinked issues within an organizational setup. Alive to policies that allow flexibility in working and social environments that are supportive, better well-being and performance of the employees in Generation Z can be enabled. This study, therefore, provides important lessons that will be useful for human resource strategies seeking to navigate effectively the dynamic work landscape today.